Force Majeure In The Perspective Of The Concept Of Justice In Modern Business Contracts: A Study Of The COVID-19 Pandemic - Tri Eka Saputra; Muh. Askaruddin Askaruddin; Nurul Qamar Nurul Qamar; Muhammad Kamal Muhammad Kamal (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study is motivated by the tension between legal certainty and justice in the application of force majeure in modern business contracts during the COVID-19 pandemic, when force majeure clauses often fail to protect structurally weaker parties. This study aims to critically examine the concept, application, and interpretation of force majeure in the Indonesian contract law system and reconstruct it as an instrument for correcting injustice that is oriented towards balancing the interests of the parties. The research uses a normative legal method with a legislative and conceptual approach, relying on the analysis of primary, secondary, and tertiary legal materials collected through literature studies and analyzed qualitatively and prescriptively. The results show that force majeure in practice is more often operated as a formalistic exculpatory mechanism than as a means of fair risk redistribution, so that the burden of pandemic losses tends to be concentrated on small businesses and parties with weak bargaining positions. Through the integration of corrective and distributive justice theories, the principle of freedom of contract, good faith, and public policy in times of crisis, this study offers a layered interpretive framework that encourages renegotiation, proportional loss sharing, and protection of vulnerable parties. These findings imply the need to redesign force majeure clauses, strengthen the orientation toward justice in contract dispute rulings, and develop policies that synergize private contracts with social justice objectives. The agenda for further research remains open